Effectiveness of chlorhexidine gels and chips in Periodontitis Patients after Scaling and Root Planing: a systematic review and Meta-analysis - Zahratul Umami Annisa; Benso Sulijaya; Ette Soraya Shahnaz Tadjoedin; Dimas Ilham Hutomo; Sri Lelyati C. Masulili (BMC, 2023)
Abstract Periodontal pockets are characteristic of periodontitis. Scaling and root planing is the gold standard for periodontitis treatment. Additional local antimicrobials are recommended in patients with a probing depth of ≥ 5 mm. This study aims to determine the effectiveness of chlorhexidine compared to other local antimicrobials in periodontitis. Searches were conducted using the Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) guidelines. Meta-analysis was performed on studies that met inclusion criteria after risk of bias assessment. Meta-analysis between chlorhexidine chips and other antimicrobials showed a mean difference in probing depth after one month of 0.58 mm (p < 0.00001) whereas after three months the mean difference in probing depth was 0.50 mm (p = 0.001), index plaque 0.01 (p = 0.94) and gingival index − 0.11 mm (p = 0.02). Between chlorhexidine gel and other antimicrobials showed a mean difference in probing depth of 0.40 mm (p = 0.30), plaque index of 0.20 mm (p = 0.0008) and gingival index of -0.04 mm (p = 0.83) after one month. Chlorhexidine chips were more effective on the gingival index than other antimicrobials after three months. The other antimicrobials were more effective than chlorhexidine chips on probing depth after one and three months, and than chlorhexidine gels on plaque index after one month.